Influence of the preparation design on the survival probability of occlusal veneers. Issue 4 (April 2022) - Schroeder, Gaëtan; Rösch, Peter; Kunzelmann, Karl-Heinz
Abstract: Objectives: The fracture resistance of ultrathin computer-aided design and computer-aided manufacturing (CAD/CAM) occlusal veneers with different preparation designs was investigated under cycling mechanical loading and via finite element analysis (FEA). Methods: Eighty molars were prepared with a circular enamel ring until complete exposure of the occlusal dentin occurred. Forty were prepared via additional circular chamfer preparation. The teeth were restored with 0.5 mm-thick occlusal veneers. Each group received a CAD/CAM fabricated occlusal veneer with a low modulus of elasticity (composite, CeraSmart) and a high modulus of elasticity material (ceramic, Celtra Duo). The restorations were adhesively luted and underwent 2000 thermocycling cycles. The samples were loaded at 50 N under 1, 000, 000 cycles in a chewing simulator and were checked for failure after various cycles. A visible crack was defined as failure, and the Kaplan-Meier survival rate was used for data analysis. One sample per group was digitized using microcomputed tomography, and FEA was performed using open-source software. The comparative stresses were analyzed for specimens with and without chamfer preparation. Results: The survival probabilities were 60% for occlusal ceramic veneers without preparation and 40% for veneers with chamfer preparation, with no statistically significant differences. Composite veneers achieved 95% survival probability regardless of the preparation method. The main principal stress in ceramic restoration was visualized via FEA. In composite veneers, stress was also visible in the luting composite and dentin. Significance: The preparation method had no influence on mechanical fatigue. Minimally invasive preparation can be recommended. The restoration material is crucial for survival.